(3QSGdI GdehMeIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdSdGe Ydi GdEeGe GdOGd Ydi Gddg MbkG MbkG GdSdGe Ydi Cejf GdHGQ hZGjI Chdi Gdfgi GdSdGe Ydi bGFe GdMb GdefJbe eef caQ hGOYi s
(3BNQgG (B:s
(3hJLGhR Yf Rddg hNWCg eZeG UJLGhRJ Yfg ef Rdd GdePfHjf adjS ddYHO Yed jJhcd ai jhe GdbjGeI aCfJ fYe Gdehdi hfYe GdbOjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B86s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds